Mizrahi voices in Musrara. - Claudia De Martino (EchoGéo)
The article analyses the social and spatial complexity of the neighbourhood of Musrara in the city of Jerusalem, before and after the major political event of the 1967 War. This article focuses on the urban and social history of the Jewish neighbourhood of Musrara and the position of an “in-between people”, as the Jewish immigrants from the Levant and Arab and Islamic countries (Mizrahim), stuck between the Arab and the Jewish people. Thus, the spatial complexity of the area, materially located at the (then) fringes of Israel, is further complicated by the presence of a marginal Jewish group, relegated by the dominant groups to the urban periphery. Yet, the 1967 War was to abruptly change the position of Musrara, turning it into a “core area”, strategically located between the Jewish city and the Arab city.